NUEVAS ESPECIES DE EXOCHONOTUS (COLEOPTERA: CLERIDAE: ENOPLIINAE) DE LA ZONA DESÉRTICA DE CHILE - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
Two new species of Exochonotus, E. barrí n.sp. and E. eugeniae n.sp. are described. A redescription of E. varipennis (Spinola 1849) and a key for the chilean species of the genus are provided. The geographical distribution of the species is established.